Life in the ponds and streams - Amos, William Hopkins (National Geographic Society)
An introduction to the animals that live in ponds and streams, including beavers, frogs, ducks, crayfish, trout, and insects.
Keywords: Pond ecology-Juvenile literature; Stream ecology-Juvenile literature; Pond animals; Stream animals; National Geographic Society (U.S.)